Perspectives of Distance Education of Future Engineers - Narzullayev Shohrukh (Researchparks Publishing, 2022)
This article focuses on the prospects of training highly qualified engineers and technicians who are able to solve important scientific and technological production tasks in higher education institutions, specialized technical schools and colleges in the republic that train all engineering personnel through distance learning educational platforms based on international standards.